Remediation of soil acidification by form of nitrogen fertilizer on grass swards of Australia and Thailand - Armour, J. D.; Berthelsen, S.; Ruaysoongnern, Sawaeng (2005)
Acidification of soil profiles from legume and N fertilized crops is a serious sustainability threat. Under tropical conditions of Northeast Thailand and Northern Australia, acidification to >90 cm has been recorded in Stylosanthes and Leucaena based pasture systems. Acidification has also been measured in other Australian cropping systems fertilized with urea or ammonium forms of N. The major processes contributing to what could be termed anthropogenic acidification are removal of base cations in the harvested product and leaching below the root zone of nitrate from ammonium and urea N fertiliser or legumes resulting in an accumulation of protons in surfaces horizons. If prophylactic applications of lime are not undertaken, acid generation in surface horizons will progressively move down the profile inducing subsoil acidification. Subsoil acidity is often difficult to correct using conventional applications of liming products. Field experiments with pastures on Acrisols in Northeast Australia (two sites) and Northeast Thailand (one site) compared the rates of alkalisation or acidification from N applied as nitrate or as urea (Australia) or ammonium sulphate (Thailand). Soil pH increased where N was applied as nitrate and decreased where N was applied as urea or ammonium sulphate. At one of the sites in Australia, regular applications of N as nitrate at 350 kg N ha-1 year-1 were made to irrigated Digitaria melanjiana cv Jarra. This significantly increased soil pH (1:5 0.01 M CaCl2) by up to 0.5 units to a depth of 0.90 m over a period of 4 years when compared to bare soil. The alkalisation of the profile was equivalent to 2.7 t/ha of calcium carbonate distributed evenly down the profile. Urea at the same rate of N decreased soil pH at 20-50 cm by 0.2 units. Similar but smaller changes were measured at the other Australian site (Brachiaria decumbens) and the site in Thailand (Andropogon gayanus cv Carimagua (Gamba grass). Treatment effects at these sites were restricted by time (1 year) or seasonal conditions that limited the number of N applications that could be applied (290 kg N/ha over 3 years) at the Thai site. The research has clearly demonstrated that nitrate N fertilizer can rapidly correct soil acidity down the soil profile to 0.9 m and this is attributed to the release of alkali from roots as nitrate is taken up. Such a strategy may be an effective approach to addressing subsoil acidification where surface applications of lime are ineffective and profile modification is cost prohibitive.